Magnesium phosphate cement prepared with electric furnace ferronickel slag: Properties and its hydration mechanism. (20th September 2021) - Luo, Zhongqiu; Ma, Yue; Mu, Weihong; Liu, Jiahui; He, Juan; Zhou, Xintao
Highlights: Electric furnace ferronickel slag was used to prepare magnesium phosphate cement. Struvite (MgNH4 PO4 ·6H2 O) is identified as the principal hydration product of EMPC. EMPC has an excellent solidification/stabilization performance of heavy metals. The properties and its formation mechanism of EMPC were researched. Abstract: High-magnesium electric furnace ferronickel slag (EFS) is an industrial solid waste, typically generated in nickel metallurgical production. This study presents an eco-friendly approach to prepare magnesium phosphate cement by using EFS as the substitute for magnesium oxide to react with ammonium dihydrogen phosphate (NH4 H2 PO4, ADP). The effects of EFS/ADP ratio and the addition of magnesium oxide on the compressive strength and setting behaviour of EFS-based magnesium phosphate cement (EMPC) are studied. The evolutions of pH and ions (Mg 2+ and PO4 3– ) concentrations of EMPC suspensions and the hydration product are investigated through inductively coupled plasma-atomic emission spectroscopy (ICP-AES), X-ray diffractometry (XRD), scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). Results show that the compressive strength of EMPC paste with the optimal formulations (EFS/ADP mass ratio of 4.0, MgO content of 3.2% and water-to-cement mass ratio (W/C) of 0.20) reach up to 33, 42, 52 and 62 MPa at 1, 3, 7 and 28 d, respectively, and the initial setting time is 7 min. Struvite (MgNH4 PO4 ·6H2 O) is identified as the principal hydration product of EMPC. The formation mechanism regarding EMPC involves the dissolution of NH4 H2 PO4, MgO and Mg2 SiO4, the precipitation of the intermediate hydrate phase and the formation of struvite as the binder phase. Moreover, EMPC paste has an excellent solidification/stabilization performance of heavy metals, and the Cr leaching concentration meets the requirement of limit value of GB 5085.3–2007 (USEPA 1311).